Covalent conjugation of cationic antimicrobial peptides with a β‐lactam antibiotic core. Issue 3 (7th March 2018) - Li, Wenyi; O'Brien‐Simpson, Neil M.; Holden, James A.; Otvos, Laszlo; Reynolds, Eric C.; Separovic, Frances; Hossain, Mohammed Akhter; Wade, John D.
Abstract: To combat the serious issue of increasing global antibiotic resistance, new antimicrobial therapies are urgently required. As one alternative, previously used antibiotics are being investigated for use in combination with more modern antibiotics including antimicrobial peptides. Towards this goal, 7‐aminocephalosporanic acid, the precursor to the conventional β‐lactam antibiotic, cephalosporin, and the related compound, 7‐aminodesacetoxycephalosporanic acid, were each chemically modified to enable their use in solid phase peptide synthesis for covalent conjugation via their 7‐amino group and a glycolic linker to the N‐terminus of a series of cationic antimicrobial peptides, MSI‐78, CA(1‐7)M(2‐9)NH2 and des‐ Chex1‐Arg20. Chemically functionalized C α ‐Fm‐protected 7‐aminocephalosporanic acid and 7‐aminodesacetoxycephalosporanic acid building blocks were separately prepared and attached by their 7‐amino group to the N‐terminus of each peptide on the solid phase via a glutaric anhydride linker. The resulting conjugated AMPs were assessed for antibacterial activity against a panel of six Gram‐negative bacteria, including clinically isolated multi‐drug resistant (MDR) pathogens. Only the conjugated MSI‐78 analogues displayed significant activity against Acinetobacter baumannii and MDR A. baumannii 156 and enhanced activity against Klebsiella pneumoniae . Further work is required to optimize the conjugation of AMPs to 7‐cephalosporanic acid and/or 7‐aminodesacetoxycephalosporanic acid to universally induce an enhanced effect on killing of drug sensitive and MDR bacterial strains that are common causes of hospital‐acquired infections. Abstract :